(untitled) (Zoological Records and Reviews, 2023)
Urbanisation is one of the most rapid and ecologically disruptive land-use changes globally, transforming natural and agricultural habitats into built environments with profound consequences for animal biodiversity. Yet the urban-rural gradient is not uniformly impoverishing for all taxonomic groups: some generalist species thrive in urban environments, while specialist taxa are eliminated, resulting in the well-documented pattern of biotic homogenisation across urbanising landscapes. This study presents a quantitative multi-taxon comparison of animal biodiversity across a fully replicated rural-urban gradient in and around Hyderabad, India – one of South Asia’s fastest-growing megacities – encompassing birds, butterflies, small mammals, herpetofauna, and ground beetles (Carabidae) at 54 sites surveyed using standardised protocols over two years (2020-2022). A total of 584 animal species were documented across five groups. Total species richness declined significantly with increasing urbanisation intensity for all groups except birds, which showed a non-linear response with highest richness at intermediate (suburban) urbanisation. Beta-diversity declined sharply along the gradient, confirming biotic homogenisation. Impervious surface cover, green space proportion, and tree canopy cover are the three strongest predictors of total animal species richness. Urban green spaces – parks, gardens, and urban forest patches – support significantly higher biodiversity than built-up matrices and serve as critical refugia for urban-sensitive species. Conservation and urban planning recommendations for biodiversity-sensitive urban development in South Asian megacities are presented.